Does health technology assessment compromise access to pharmaceuticals? - Melanie Büssgen; Tom Stargardt (The European Journal of Health Economics, 2022)
In response to rapidly rising pharmaceutical costs, many countries have introduced health technology assessment (HTA) as a 'fourth hurdle'. We evaluated the causal effect of HTA based regulation on access to pharmaceuticals by using the introduction of Germany's HTA system (AMNOG) in 2011. We obtained launch data on pharmaceuticals for 30 European countries from the IQVIA (formerly IMS) database. Using difference-in-difference models, we estimated the effect of AMNOG on launch delay, the ranking order of launch delays, and the availability of pharmaceuticals. We then compared the results for Germany to Austria, Czechia, Italy, Portugal, and the UK. Across all six countries, launch delays decreased from the pre-AMNOG period (25.01~months) to the post-AMNOG period (14.34~months). However, the introduction of AMNOG consistently reduced the magnitude of the decrease in launch delay in Germany compared to the comparator countries (staggered DiD:0.167em+0.167em4.31~months, p 0.167em=0.167em0.05). Our logit results indicate that the availability of pharmaceuticals in Germany increased as a result of AMNOG (staggered logit:0.167em+0.167em5.78%, p 0.167em=0.167em0.009). We provide evidence on the trade-off between regulation and access. This can help policymakers make better-informed decisions to strike the right balance between cost savings achieved through HTA based regulation and access to pharmaceuticals.
Keywords: I18; 610; AMNOG; Launch delay; Pharmaceuticals; HTA; Health policy; Price regulation